Efektifitas Metode Pembelajaran Snowball Throwing Pada Mata Pelajaran IPA Kelas V SDIT Al Azhar Kota Kediri - Makhfud; Ali Imron (eL Bidayah: Journal of Islamic Elementary Education, 2020)
One of the learning problems is the accuracy of the teacher using the learning method. For schools, these problems are always motivated by the inability of teachers to choose and implement learning methods. In this context, it is important to study the effectiveness of the Snowball Throwing method in science subjects at SDIT AL Azhar Kediri. In order to obtain research results, the method used by researchers is descriptive qualitative. The data sources produced were the results of interviews, observations and document analysis. All data are processed and educated to be presented as research results. The results showed, the effectiveness of the Snowball Throwing learning method in science subjects at SDIT Al Azhar Kota Kediri is that it can improve student learning outcomes, the learning process becomes more enjoyable, can increase interest and motivation to learn, and can make students actively involved in learning. [Salah satu permasalahan pembelajaran adalah ketepatan guru menggunakan metode pembelajaran. Bagi sekolah, permasalahan tersebut selalu dilatar-belakangi oleh ketidak mampuan guru dalam memilih dan melaksanakan metode pembelajaran. Dalam konteks inilah, penting mengkaji efektivitas metode Snowball Throwing pada mata pelajaran IPA di SDIT AL Azhar Kota Kediri. Guna mendapatkan hasil penelitian, metode yang dilakukan peneliti adalah kualitatif diskriptif. Sumber data yang dihasilkan adalah hasil wawancara, pengamatan dan analisis dokumen. Semua data diolah dan diredukasi untuk dipaparkan sebagai hasil penelitian. Hasil penelitian menunjukkan, efektifitas metode pembelajaran Snowball Throwing pada mata pelajaran IPA kelas SDIT Al Azhar Kota Kediri adalah dapat meningkatkan hasil belajar siswa, proses pembelajaran menjadi lebih menyenangkan, dapat meningkatkan minat dan motivasi belajar, serta dapat membuat siswa terlibat aktif dalam pembelajaran]